The foundations of mathematics in the theory of sets - Mayberry, John P.; Cambridge (Online service). (Cambridge Cambridge University Press, 2001)
This unified approach to the foundations of mathematics in the theory of sets covers both conventional and finitary (constructive) mathematics. It is based on a philosophical, historical and mathematical analysis of the relation between the concepts of natural number and set. The book contains an investigation of the logic of quantification over the universe of sets and a discussion of its role in second order logic, and the analysis of proof by induction and definition by recursion. The book should appeal to both philosophers and mathematicians with an interest in the foundations of mathematics.
Electronic reproduction.
Keywords: Set theory